Interactivity, game creation, design, learning, and innovation : 7th EAI International Conference, ArtsIT 2018, and 3rd EAI International Conference, DLI 2018, ICTCC 2018, Braga, Portugal, October 24-26, 2018, Proceedings /: 7th EAI International Conference, ArtsIT 2018, and 3rd EAI International Conference, DLI 2018, ICTCC 2018, Braga, Portugal, October 24-26, 2018, Proceedings. (2019) - Unknown
No abstract available